Genetic profile of progressive myoclonic epilepsy in Mali reveals novel findings - Cissé, Lassana; Bamba, Salia; Diallo, Seybou H.; Ji, Weizhen; Dembélé, Mohamed Emile; Yalcouyé, Abdoulaye; Coulibaly, Toumany; Traoré, Ibrahima; Jeffries, Lauren; Diarra, Salimata; Maiga, Alassane Dit Baneye; Diallo, Salimata; et al. (Frontiers in Neurology, 2024)
Background and objectives Progressive myoclonic epilepsy (PME) is a group of neurological disorders characterized by recurrent myoclonic seizures with progressive neurological deterioration. We investigated the genetics of three unrelated patients with PME from Mali, a country in sub-Saharan Africa highly underrepresented in genetic and genomic research. Methods Participants were carefully examined and phenotyped. DNA was obtained for genetic analysis including whole exome sequencing (WES). In silico prediction tools and ACMG criteria were used to assess the deleteriousness of putative candidate variants. Results Pedigree analysis suggests autosomal recessive inheritance patterns for one family and sporadic forms of PME for the two other cases. WES identified novel homozygous missense variants in all the three patients, one each for NHLRC1, EPM2A, and NEU1. The sequence variants segregated with PME in each family and in silico studies including protein 3D structures, CADD scores and ACMG criteria suggested that they were damaging. Discussion PME is a group of clinically heterogeneous neurological disorders. Most reported cases in the literature are from European background with only a few cases described in North Africa. We report here novel pathogenic variants in three different genes causing PME phenotypes in three unrelated Malian patients, suggesting that genetic studies of underrepresented populations may expand the genetic epidemiology of PME. These findings also emphasize the need for inclusive genetic research to ensure a more targeted diagnostic and therapeutic approaches for diverse patient populations.